Analisis Hubungan Faktor Fisik dan Psikososial terhadap Keluhan Gangguan Otot Tulang Rangka Akibat Kerja pada Guru SMK Negeri di Kota Pekanbaru - Florensia, Maria Yolanda; Widanarko, Baiduri (UI Scholars Hub, 2022)
Work-related musculoskeletal disorders (WMSDs) are one of the most common occupational health problems among workers, including teachers. High work demand and awkward posture are among the most common risk factors. In addition, individual characteristics are included as risk factors that can increase these complaints. Thus, the purpose of this research is to analyze the relationship between individual characteristics, physical and psychosocial risk factors against WMSDs on teachers at State Vocational High School. This research was conducted in April – July 2021 using various questionnaires like NMQ, QEC, and a combination of psychosocial questionnaires. A cross-sectional study design was used in this research with 100 teachers involved from three State Vocational High School in Pekanbaru. The results of this research indicate that there are three variables that have a significant relationship, namely: a high level of risk on wrist/hand and low control of work with neck complaints and low social support with shoulder complaints. Therefore, further control and intervention are needed to overcome these problems.